'Rural–Urban Alliance' as a new model for post-disaster social work intervention in community reconstruction: The case in Sichuan, China. (September 2015) - Ku, Hok Bun; Ma, Yu Na
On 12 May 2008, a huge earthquake struck Wenchuan county in Sichuan province, China. Since that time, we have worked together with the local community, implementing an alternative model of community reconstruction. Our 'rural–urban alliance' is an action research project devoted to post-disaster community rebuilding, which not only restores local livelihoods but also creates sustainable economic development. This article examines the role of social workers in disaster intervention, the theoretical background of our new model and the history of the intervention itself.